Forecasting soccer matcheswith betting odds: A tale of two markets - Tadgh Hegarty; Karl Whelan (University College Dublin, UCD School of Economics, 2023)
We compare the properties of betting market odds set in two distinct markets for a large sample of European soccer matches. We confirm inefficiencies in the traditional market for bets on a home win, an away win or a draw as found in previous studies such as Angelini and De Angelis (2019), in particular that there is a strong pattern of favourite-longshot bias. Conversely, we document how a betting market that has emerged in recent years, the Asian handicap market, can generate efficient forecasts for the same set of matches using a new methodology for mapping its odds into probabilities.
Keywords: G14; L83; Z20; Z21; 330; Sports Forecasting; Betting Markets; Market Efficiency; Asian Handicap